Conducting Job Analysis for University Student Ambassador and Peer Mentor - Andhika Alexander Repi (Jurnal Manajemen Indonesia, 2021)
Student Ambassador and Peer Mentor are two positions, which play important role for university. Student Ambassador play role in providing information for prospective student and help new arrivals student settle in, also make the most out of their time while at University, while Peer Mentor help the student to develop student’s academic track record. Both of this position must clearly know and understanding their job, tasks and responsibilities. In fact, an overload and overlapping job was experience by these two positions. Unclear and miss understanding about job and role became a root-problem. The purpose of this research is to design and analyse the job of Student Ambassador and Peer Mentor. Qualitatives used as a research method with questioner, interview, and documentation study were adopted as a collecting data method. The participants of this research are the jobholder and the supervisor of Student Ambassador and Peer Mentor. Research result is job analysis document for Student Ambassador and Peer Mentor provided and it consists of job description and job specification. Document of Student Ambassador and Peer Mentor Job Analysis has been approved the university. For future direction, effectiveness of job analysis and it relation with Student Ambassador and Peer Mentor performance must be research. Job analysis based on competences could be a suggestion for further work. Keywords— Job Analysis; Job Description; Job Specification; Human Resources Management Student Ambassador; Peer-Mentor Program